Caracterización De Factores Asociados a La Presencia Del Trastorno Negativita Desafiante en los Estudiantes de Sexto Grado del Colegio I.E.D Jose Martí Sede B (2015)
This research aims at the characterization of factors associated with the presence of oppositional defiant disorder in children sixth grade students of the school IED José Marti. Initially a theoretical review, based on child psychopathology from the dimensional approach proposed by Achenbach and Rescorla and who also designed screening tool Youth Self Report questionnaire aimed at identifying symptoms grouped into different clinical syndromes associated disorders is diagnosed by the Diagnostic and Statistical Manual of Mental Disorders DSM-IV. The sample in this study was 47 sixth graders campus (21 girls and 26 boys) aged between 10 and 15 years with a statistical average of 12.5. the methodology used in this research is descriptive, nonexperimental cross-sectional design. The results obtained in this study show the existence of cases in which one can determine the presence of oppositional defiant disorder where males had more cases than female.